David Conner papers - Conner, David, 1792-1856.
Corrrespondence, reports, invoices, ships returns, extracts from ships logs, and other official naval papers primarily pertaining to Conner's service as commander of U.S. naval forces in the Caribbean and the Gulf of Mexico. Many of the letters are from commanders of vessels, such as the Bainbridge, Falmouth, Porpoise, Potomac, and Vandalia. Includes material relating to the 1844 revolution in the Dominican Republic, naval operations in the Mexican War, and preparations for the attack on Veracruz Llave, Mexico, where Conner managed the landing of General Winfield Scott's army. Correspondents include John H. Aulick, George Bancroft, Franklin Chase, W.H. Chase, John S. Chauncey, Joseph Gideon, James William Glass, John Gwinn, William E. Hunt, W. Latimer, E.A.F. Lavallette, Henri Levi, John Y. Mason, Joseph Mattison, John L. Saunders, and Winfield Scott.
In part, transcripts.
Naval officer.
Collection material in English.
Keywords: Aulick, John H., -- -1873 -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Chase, Franklin -- Correspondence; Chase, W. H. -- 1798-1870 -- Correspondence; Chauncey, John S., -- -1871 -- Correspondence; Gideon, Joseph -- Correspondence; Glass, James William, -- approximately 1825-1855 -- Correspondence; Gwinn, John, -- 1791-1849 -- Correspondence; Hunt, William E. -- Correspondence; Latimer, William K., -- -1873 -- Correspondence; Lavallette, E. A. F. -- approximately 1790-1862 -- Correspondence; Levi, Henri -- Correspondence; Mason, John Y. -- 1799-1859 -- Correspondence; Saunders, John Loyall, -- -1860 -- Correspondence; Mattison, Joseph -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; United States. -- Navy -- History -- 19th century; Bainbridge (Brig); Falmouth (Ship); Porpoise (Schooner); Potomac (Frigate); Vandalia (Sloop); Mexican War, 1846-1848 -- Naval operations, American; Ship's papers -- 19th century; Caribbean Area -- History, Naval -- 19th century; Dominican Republic -- History -- 1844-1930.; Gulf Coast (U.S.) -- History, Naval -- 19th century; Mexico, Gulf of -- History, Naval -- 19th century; Veracruz (Veracruz-Llave, Mexico) -- History -- Surrender, 1847.; Naval officers